A framework for regenerative energy supply options for Africa - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
The framework has been finalized and published in the Journal Sustainability. Duguma L, Kamwilu E, Minang PA, Nzyoka J, Muthee K. Ecosystem-Based Approaches to Bioenergy and the Need for Regenerative Supply Options for Africa. Sustainability. 2020; 12(20):8588. https://doi.org/10.3390/su12208588